Application of ionizing radiation in the “licuri” (Syagrus coronata (Mart.)) as phytosanitary treatment of the Pachymerus nucleorum beetle (Fabricius, 1792) (Brazilian Journal of Radiation Sciences, 2021)
Pachymerus nucleorum (Fabricius, 1792), is a pest of economic importance it causes direct damages to the “licuri” almonds. The objective of this study was to determine the lethal doses of gamma radiation for stages egg, larvae, and pupae of this insect as a phytosanitary treatment in “licuri”. The samples were irradiated in a Cobalt 60 irradiator, Gammacell-220 type, installed at the Institute of Energy and Nuclear Research - IPEN / CNEN at a dose rate of 748 Gy / h. Each treatment consisted of 3 replicates, so 180 licuri were irradiated in the doses of 50, 75, 100, and 125 Gy. After irradiation, the samples were stored at a temperature of 25 ± 5°C and relative humidity of 70 ± 5%. The evaluation of the fruits was performed by the emergence of insects. It is concluded that the dose of 125 Gy was sufficient to inhibit the development of insect life stages. Therefore, this dose of radiation can be used for control of the immature stages of the P. nucleorum.
Keywords: food irradiation; insects; life stage.